Electrical Energy Storage From First Principles - Jiang, Zhijun; Xu, Bin; Prosandeev, Sergey; Íñiguez, Jorge; Xiang, Hongjun; Bellaiche, L. (Frontiers in Electronic Materials, 2022)
Dielectric capacitors are particularly suitable to store electrical energy of a fast-changing nature. Here we present a review of recent applications of first-principles and first-principles-based effective Hamiltonian approaches to the study of energy storage in ferroelectrics, lead-free antiferroelectrics, relaxor ferroelectrics and nitride semiconductors. Specifically, these approaches are used to investigate the energy density and efficiency in perovskite BaTiO3, PbTiO3 and KNbO3 ferroelectrics, Bi1−xRxFeO3 antiferroelectric solid solutions (where R is a rare-earth ion), Ba(Zr,Ti)O3 relaxor ferroelectrics, and epitaxial AlN/ScN superlattices. Ultrahigh energy densities and efficiencies are predicted in some of these compounds. In addition, phenomenological models are used to analyze and understand these energy storage results. Consequently, the numerical methods and simple models detailed here can be easily employed to design novel nonlinear dielectrics with further enhanced energy storage performance.